Veins System and Their Mineralogical and Microthermometric Characteristics within The Humpa Leu East Porphyry Copper-Gold Mineralization at Hu'u District, Sumbawa Island, Indonesia - Verdiansyah, Okki (Universiti Teknologi Malaysia, 2022)
The study area, i.e Humpa Leu East is a porphyry prospect located in Hu'u district, Sumbawa Island, Indonesia. This study is aimed to understand the characteristics of veins, the distribution of veins and mineralogy, microthermometric conditions of ore fluids, distribution of elements, and their implications for exploration and deposit model. The Hu'u district is a paleovolcano member of the Miocene to Plio-pleistocene volcanic rocks. Hydrothermal alteration evolved to get out from the tonalitic body, consists of potassic, propyllitic and overprinted by phyllic and advanced argillic. The mineralization is dominated by chalcopyrite, associated with quartz±anhydrite veins, and hydrothermal breccia. Hydrothermal fluids temperature measured at the value of 109.9 °C-525.3 °C and > 550 ° C with an averaging range of Th is 296.5-329.7 °C, and salinity of 10.9 wt NaCl eq. Quartz veins occur as a package or series of porphyry type veins designated as EDM-M1-A1, A2-A3-Apsb-anh, A3-A2, M2-Apsb-A2-A3, M1-B-C, C-D-anhydrite, and epithermal veins. Hydrothermal fluids possibly have mixed by high-temperature hyper-saline fluids to medium temperature low saline fluids. The Humpa Leu East can be identified as a 'push-up porphyry system' that still remains more extensive system underneath or in the side area. These results can be used for understanding the texture of veins as a vectoring to ore, metal distribution in veins and rocks. Early type veins such as type A have more intensive metal content and are followed by type B, C and weaken until the latest stage. © 2022 Penerbit UTM Press. All rights reserved.